In vitro anticancer potentials of ethyl p-methoxycinnamate (EPMC) an active ingredient of cekur (Kaempferia galanga) on human oral cancer cell lines differing in p53 status. - Ichwan, Solachuddin J. A.; Omar, Muhammad Nor; Kasmuri, Abdul Razak (2018)
Oral Squamous Cell Carcinoma (OSCC) is one of malignant tumors with poor prognosis resulting in major morbidity and mortality. Loss of p53 tumor suppressor function is a common event in numerous types of human cancer including OSCC and the status of the p53 has been known to play a role in resistance against chemotherapy. Herbal remedies are known to provide lead compounds in the past and play a significant role in future in the treatment of cancer due to their minimal side effects. Kaempferia galanga is one of the herbal plant that have many medicinal properties. The plant extract has also been reported to possess in vitro anti-cancer activities on various cancer cell lines. Ethyl-p-methoxycinnamate (EPMC), a major component of Kaempferia galanga has been attributed to its medicinal benefits. We report here for the first time the anticancer potential of EPMC on oral cancer cells derived from human oral cavity, HSC-3 and Ca922 lines. MTT assay results showed that EPMC markedly induced cytotoxicity on HSC-3 (IC50 0.075 mg/mL) and Ca922 (IC50 0.085 mg/mL) cell lines. The apoptotic activity induced by EPMC was detected in both cell lines by flow cytometry and confirmed with Caspase 3/7 assay. Moreover, quantitative RT-PCR analysis revealed that EPMC-induced apoptosis in both lines elevated the mRNA levels of pro-apoptotic genes caspase-9 and p53 target-PUMA. These results suggest that EPMC may be a potential candidate for oral cancer treatment.